ChemInform Abstract: Magnesium Oxide Nanotubes: Synthesis, Characterization and Application as Efficient Recyclable Catalyst for Pyrazolyl 1, 4‐Dihydropyridine Derivatives. Issue 1 (3rd January 2013) - Murugan, R.; Ramamoorthy, K.; Sundarrajan, S.; Ramakrishna, S.
Abstract A mild, cost effective, and highly efficient catalyst is presented for the rapid, simple, and cleaner title reaction which includes an easy work‐up procedure.